The Effectiveness of Leadership Style and Compensation on Employee Performance with Job Comfort as an Intervening Variable at PT. Permodalan Nasional Madani Mekaar Asahan Area - Weni Mega Sari; Siti Safaria (Formosa Journal of Sustainable Research, 2023)
Effectiveness of leadership, compensation, on employee’s performance with work leisure as intervening variable at PT Permodalan Nasional Madani Mekaar Asahan Area. The results are Leadership style affecting job comfort. Leadership Style affecting Employee’s Performance, Work Comfort affecting Employee Performance, Compensation affecting Work Comfort, Compensation affecting Performance. Work Comfort significantly mediates the ties between Leadership Style, Work Comfort significantly mediates the ties between Compensation and Employee’s Performance